2017
DOI: 10.1016/j.molcel.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Hippo-YAP Pathway by Glucose Sensor O-GlcNAcylation

Abstract: The Hippo pathway is crucial in organ size control and tissue homeostasis, with deregulation leading to cancer. An extracellular nutrition signal, such as glucose, regulates the Hippo pathway activation. However, the mechanisms are still not clear. Here, we found that the Hippo pathway is directly regulated by the hexosamine biosynthesis pathway (HBP) in response to metabolic nutrients. Mechanistically, the core component of Hippo pathway (YAP) is O-GlcNAcylated by O-GlcNAc transferase (OGT) at serine 109. YAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
196
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(211 citation statements)
references
References 68 publications
12
196
2
1
Order By: Relevance
“…However, two recent reports have revealed a novel post-transcriptional modification of YAP regulated by the hexosamine biosynthesis pathway (HBP) in response to metabolic nutrients (Fig. 2b) [30, 31]. The HBP is an important glucose metabolism pathway, which controls metabolic flux and O-GlcNAcylation.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two recent reports have revealed a novel post-transcriptional modification of YAP regulated by the hexosamine biosynthesis pathway (HBP) in response to metabolic nutrients (Fig. 2b) [30, 31]. The HBP is an important glucose metabolism pathway, which controls metabolic flux and O-GlcNAcylation.…”
Section: Main Textmentioning
confidence: 99%
“…In high glucose conditions, O-GlcNAc transferase (OGT), which is a key enzyme of the HBP, O-GlcNAcylates YAP at different O-GlcNAc sites, such as Ser109 and Thr241, while the TAZ could not be O-GlcNAcylated. YAP O-GlcNAcylation promotes its expression, enhances its stability, prevents its phosphorylation, and activates its transcriptional activity [30, 31]. Mechanistically, Peng et al found that YAP O-GlcNAcylation prevents LATS1-induced YAP phosphorylation by directly blocking its interaction with LATS1, the O-GlcNAcylation of YAP does not compete with phosphorylation at serine 109, it indicates that perhaps glycosylation is the main modification and functional regulator rather than phosphorylation at serine 109 [30].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of GFPT1 protein (HBP) using this method blocks nuclear localization of YAP1 ( Figure 5G, H) but has no effect on AP-2γ expression ( Figure 5K requires O-linked glycosylation at 1-4 specific sites on the protein (Peng et al, 2017;. This is a likely explanation for loss of YAP1 localization when this protein modification is blocked.…”
Section: Molecular Mechanisms Linking Glucose Metabolism To Cdx2 Exprmentioning
confidence: 99%
“…In contrast, a protein phosphatase PP2A complex called STRIPAK (Bae et al, ; Praskova et al, ; Zheng et al, ), Dachsous–Fat system (Irvine & Harvey, ; Mao et al, ), and extracellular matrix (ECM) sensing integrins (Chakraborty & Hong, ; Dobrokhotov, Samsonov, Sokabe, & Hirata, ) are responsible for inactivation of the Hippo pathway. In high‐energy conditions, enzyme O‐GlcNac transferase deactivates Hippo signaling allowing the expression of YAP‐regulated growth‐promoting genes (Peng et al, ). This signaling pathway is also deactivated by Ajuba LIM proteins (Das Thakur et al, ; Rauskolb, Sun, Sun, Pan, & Irvine, ), by changes in actomyosin contractility under mechanical stress conditions (Furukawa, Yamashita, Sakurai, & Ohno, ) and by HIF‐1α in hypoxic conditions (Xiang et al, ).…”
Section: Overview Of the Hippo Signaling Networkmentioning
confidence: 99%